Dialogics of the Oppressed. - Hitchcock, Peter (University of Minnesota Press, 1992)
Formulated within and against the context of Russian formalism that became the backbone of semiotics, Mikhail Bahktins work has enabled contemporary critical theories to return to specific sociopolitical and historical moments that had been closed off by formalist abstractions. In Dialogics of the Oppressed, Peter Hitchcock looks through the lens of Bakhtins theory of dialogism for an analysis of subaltern writing. Rather than assume an integral "subaltern subject" as the object of analysis, Hitchcock - in case studies of four global feminists, Nawal el Saadawi, Pat Barker, Zhang Jie, and Ag.